2019
DOI: 10.1021/acs.langmuir.9b00099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Concentration of 1-Pentanol on the Wettability of Petroleum Fluid–Brine–Rock Systems

Abstract: High-concentration brines generally cause the wettability of petroleum fluid–brine–rock systems to become less water-wet (more oil-wet). The addition of alcohols to the brine, however, may produce an opposite effect. In this work, we investigate the synergic effects of a low concentration of 1-pentanol and brines on the wettability of petroleum fluid–brine–rock systems. The variables examined include the mineral type (mica, quartz, calcite), brine concentration (0–3 M), ion type (monovalent and divalent), crud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 35 publications
6
28
0
Order By: Relevance
“…Similarly, the contact angle of the oil droplet on the calcite surface reduces from 162°to 103°F at 140 °C and 40 MPa. This observation is in line with the work of Lu et al 13 who report that adding 1-pentanol alcohol (1 wt %) to high salinity brine (1 M NaCl) reduces the contact angle of the oil droplet on the calcite surface from 135°( without 1-pentanol) to 70°, a 65°reduction, with a strong shift of the wettability from a strongly oil-wet system toward a weakly water-wet system, although they did not test at high temperature and high pressure. This observation is also in agreement with our previous study, 14 showing that the contact angle of oil−brine−calcite reduces from 165°to 125°while mixing 1-pentanol alcohol (1 wt %) to high salinity brine (1 mol NaCl + 0.01 mol CaCl 2 ) at ambient conditions.…”
Section: ■ Introductionsupporting
confidence: 94%
See 2 more Smart Citations
“…Similarly, the contact angle of the oil droplet on the calcite surface reduces from 162°to 103°F at 140 °C and 40 MPa. This observation is in line with the work of Lu et al 13 who report that adding 1-pentanol alcohol (1 wt %) to high salinity brine (1 M NaCl) reduces the contact angle of the oil droplet on the calcite surface from 135°( without 1-pentanol) to 70°, a 65°reduction, with a strong shift of the wettability from a strongly oil-wet system toward a weakly water-wet system, although they did not test at high temperature and high pressure. This observation is also in agreement with our previous study, 14 showing that the contact angle of oil−brine−calcite reduces from 165°to 125°while mixing 1-pentanol alcohol (1 wt %) to high salinity brine (1 mol NaCl + 0.01 mol CaCl 2 ) at ambient conditions.…”
Section: ■ Introductionsupporting
confidence: 94%
“…This is also in line with our previous work, 14 which illustrates that the contact angle of the oil droplet on the calcite surface reduces from 105°to 90°. Analogously, Lu et al 13 reported that the contact angle of the oil droplet on the calcite surface reduces to 23°w hen mixing 1-pentanol alcohol (1 wt %) with low salinity brine (0.01 M NaCl). Moreover, similar to HS brine, Figure 8 demonstrates that increasing the temperature increases the contact angle and, thus, the hydrophobicity in LS brine with 1pentanol alcohol (1 wt %).…”
Section: ■ Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition to surfactant, alcohol solution was studied in the literature for wettability alteration. Lu et al presented a study of 1-pentanol solution for wettability alteration . Their experimental results showed that the contact angle of a petroleum fluid on calcite was significantly decreased in 1 wt % 1-pentanol solution.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al presented a study of 1-pentanol solution for wettability alteration. 26 Their experimental results showed that the contact angle of a petroleum fluid on calcite was significantly decreased in 1 wt % 1-pentanol solution. The effect was more evident with 0.5 wt % 1-pentanol at a high NaCl or MgCl 2 concentrations.…”
Section: Introductionmentioning
confidence: 99%